REKONSTRUKSI SISTEM PEMILU PRESIDEN PASCA PUTUSAN MK NO. 62/PUU-XXII/2024 TENTANG AMBANG BATAS PENGUSULAN CALON PRESIDEN DAN WAKIL PRESIDEN - Mahmudi, Mohammad; Rahman, Fathor (HUNILA : Jurnal Ilmu Hukum dan Integrasi Peradilan, 2025)
This study aims to analyze the impact of the Constitutional Court’s (MK) Decision No. 62/PUU-XXII/2024 on Indonesia’s presidential election system, particularly regarding the removal of the presidential candidacy threshold. The research methodology employed is a normative juridical approach, analyzing laws, judicial decisions, and legal doctrines. The study utilizes primary legal materials, including the 1945 Constitution of the Republic of Indonesia, the Election Law, and relevant Constitutional Court decisions, as well as secondary legal materials such as legal journals, books, and academic articles. Data was collected through library research and qualitatively analyzed to understand the legal implications and political impacts of the decision. The results indicate that this decision opens broader opportunities for presidential candidates to run without having to meet the support requirements outlined in Article 222 of the Election Law, thus increasing competition and choices for voters. However, this change may also lead to greater political fragmentation and reduced political consolidation, which could threaten post-election governmental stability. The study provides recommendations related to enhancing democracy education, improving the two-round election system, strengthening the roles of the General Elections Commission (KPU) and Election Supervisory Agency (Bawaslu), as well as monitoring political fragmentation following the electoral system change. The findings are expected to provide solutions for policymakers in designing a more inclusive and efficient election system in Indonesia.